A separator material for lithium batteries and a method for producing the same
Patent Information
- Application Number
- CN202511041147.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-28
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-07-28
AI Technical Summary
在锂离子电池组装过程中,干燥的环境会造成陶瓷涂层失水,而对基膜产生拉应力,导致隔膜向涂层方向发生卷曲,从而影响电芯生产的效率和良率
0、本发明中改性纳米TiO2复合材料以纤维素纳米晶、锆酸镧和稀土镨为改性剂,纳米TiO2为原料制得,其中纤维素纳米晶表面含有丰富的羟基,通过化学改性(如酯化、醚化、硅烷化等)可以引入疏水基团或聚合物链,从而改善其在疏水性聚合物中的分散性和相容性,纤维素纳米晶具有生物降解性和可再生性,作为环保型改性剂,可替代传统化石基聚合物,减少对环境的影响。纤维素纳米晶作为载体或模板,纤维素纳米晶可以诱导合成介孔TiO2,提高其比表面积和孔隙率,从而增强其光催化性能。锆酸镧作为掺杂剂,锆酸镧可以改善TiO2的晶格结构,抑制其向金红石相的转变,从而提高其光催化活性。稀土镨与镧类似,镨作为稀土元素之一,其掺杂同样可以提高TiO2的光催化活性。纤维素纳米晶作为结构调控剂,可以优化TiO2的形貌和孔结构;而锆酸镧和稀土镨作为掺杂剂,可以改善其电子结构和光吸收性能。三者协同作用,进一步提升纳米TiO2的光催化效率和稳定性。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery technology, and more specifically, to a separator material for lithium batteries and its preparation method. Background Technology
[0002] Lithium-ion batteries have advantages such as high specific energy, long cycle life, and no memory effect, and are widely used in many fields such as new energy vehicles, aerospace, and military. As an important component of lithium-ion batteries, the separator plays an electronic insulating role between the positive and negative electrodes, while ensuring the free movement of ions. Although the separator does not directly participate in the electrochemical reaction of the battery, its structure and performance play an important role in the battery's cycle life, safety, energy density, and power density.
[0003] Because ceramic coatings contain hydrophilic groups such as hydroxyl groups, they are prone to absorbing or losing water in humid or dry environments. During lithium-ion battery assembly, a dry environment can cause the ceramic coating to lose water, resulting in tensile stress on the base film. This causes the separator to curl towards the coating, thus affecting the efficiency and yield of cell production. Summary of the Invention
[0004] This invention provides a separator material for lithium batteries and its preparation method. By adding modified nano-TiO2 composite material, nanoparticles are introduced into the separator to form a three-dimensional network structure, which improves the liquid absorption and ionic conductivity of the separator. At the same time, it has high air permeability and good mechanical properties and ionic conductivity.
[0005] In a first aspect, the present invention provides a separator material for lithium batteries, comprising a base film and a modified nano-TiO2 coating, wherein the modified nano-TiO2 coating is disposed on at least one side surface of the base film, and the modified nano-TiO2 coating comprises the following raw materials in parts by weight: 55-80 parts of modified nano-TiO2 composite material, 8-24 parts of binder, and 2.5-7.5 parts of dispersant; the modified nano-TiO2 composite material is prepared by using cellulose nanocrystals, lanthanum zirconate and rare earth praseodymium as modifiers and nano-TiO2 as raw material; the mass ratio of the cellulose nanocrystals, lanthanum zirconate and rare earth praseodymium is 1-5:2-3:1.
[0006] Preferably, the preparation method of the modified nano-TiO2 composite material includes the following steps: S1: Disperse cellulose nanocrystals in water, add nano-TiO2 suspension, the mass ratio of cellulose nanocrystals to nano-TiO2 is 1:3-5, and sonicate to obtain the composite. S2: Lanthanum zirconate and rare earth praseodymium were prepared by ion doping to obtain lanthanum zirconate loaded with rare earth praseodymium. S3: The composite was dispersed in ethanol, lanthanum zirconate-supported rare earth praseodymium powder was added, ultrasonic treatment was performed, tetrabutyl titanate was added dropwise, and the mixture was stirred to form a gel. After drying, the modified nano-TiO2 composite material was obtained.
[0007] Preferably, the base membrane is a polyolefin microporous membrane.
[0008] Preferably, the adhesive comprises a soft monomer and a hard monomer, the soft monomer comprising acrylates, and the hard monomer comprising one or more of (meth)acrylonitrile, acrylonitrile, styrene, and (meth)acrylates, wherein the molar ratio of the soft monomer to the hard monomer is 1.5-6.3.
[0009] Preferably, the dispersant is one or more of sodium polyacrylate, lithium polyacrylate, potassium polyacrylate, and ammonium polyacrylate.
[0010] Preferably, the mixture also includes a wetting agent and a thickener, wherein the wetting agent is a silanol nonionic surfactant and the thickener is sodium hydroxymethyl cellulose.
[0011] In a second aspect, the present invention provides a method for preparing a separator material for lithium batteries, comprising the following steps: (1) Weigh each raw material according to the weight parts, dissolve the binder in N-methylpyrrolidone, add the modified nano-TiO2 composite material, dispersant, wetting agent and thickener, mix and disperse in a ball mill jar to obtain nano-TiO2 composite material coating slurry; (2) The nano-TiO2 composite material coating slurry is coated on one side of the base film, dried and rolled up to prepare a lithium-ion battery separator.
[0012] Preferably, the thickness of the nano-TiO2 composite material coating on one side is 2.0-5.0 μm.
[0013] Thirdly, the present invention provides a lithium-ion battery, including the aforementioned separator material for lithium batteries.
[0014] In summary, the present invention has the following beneficial effects: 0. The modified nano-TiO2 composite material in this invention is prepared using cellulose nanocrystals, lanthanum zirconate, and rare earth praseodymium as modifiers and nano-TiO2 as raw material. The cellulose nanocrystals contain abundant hydroxyl groups on their surface, which can be chemically modified (e.g., esterification, etherification, silanization) to introduce hydrophobic groups or polymer chains, thereby improving their dispersibility and compatibility in hydrophobic polymers. Cellulose nanocrystals are biodegradable and renewable, and as an environmentally friendly modifier, they can replace traditional fossil-based polymers, reducing environmental impact. Cellulose nanocrystals serve as a carrier or template, inducing the synthesis of mesoporous TiO2, increasing its specific surface area and porosity, thus enhancing its photocatalytic performance. Lanthanum zirconate, as a dopant, can improve the lattice structure of TiO2 and inhibit its transformation to the rutile phase, thereby improving its photocatalytic activity. Similar to lanthanum, praseodymium, as a rare earth element, can also enhance the photocatalytic activity of TiO2 through doping. Cellulose nanocrystals, acting as structure modifiers, can optimize the morphology and pore structure of TiO2; while lanthanum zirconate and rare-earth praseodymium, as dopants, can improve its electronic structure and light absorption performance. The synergistic effect of these three components further enhances the photocatalytic efficiency and stability of nano-TiO2.
[0015] 2. The high specific surface area and porous structure of nano-TiO2 in the modified nano-TiO2 composite material of this invention can significantly reduce the resistance to electron and lithium-ion transport, thereby improving the conductivity of the electrode material and the lithium-ion diffusion rate. The porous structure and high specific surface area of nano-TiO2 can increase the contact area between the electrode material and the electrolyte, thereby reducing charge transfer resistance and improving the reversible insertion and extraction capabilities of lithium ions. Nano-TiO2 has a positive impact on the electrochemical performance of lithium battery separators by improving ionic conductivity, enhancing electrochemical stability, improving mechanical properties, optimizing liquid absorption and porosity, improving cycle stability and rate performance, and reducing interfacial impedance.
[0016] 3. The nano-TiO2 composite system of this invention introduces nanoparticles into the separator, forming a three-dimensional network structure, thereby improving the separator's liquid absorption and ionic conductivity. The nano-TiO2 surface undergoes Lewis acid-base interactions with components such as carbonates in the electrolyte, promoting the dissociation of Li⁺ and thus forming an interfacial phase enriched with "free" Li⁺ at the particle / electrolyte interface, increasing the Li⁺ transport rate. Through grafting modification, nano-TiO2 can form active sites on the separator surface, enhancing the separator's wettability and thermal stability. The nano-TiO2 composite system significantly improves the thermal stability, ionic conductivity, and mechanical properties of the lithium battery separator through modification, thereby improving the battery's cycle stability and rate performance.
[0017] It should be understood that the above general description and the following detailed description are exemplary and explanatory only, and do not limit the scope of protection of the present invention. Detailed Implementation
[0018] The present invention will be further described in detail below with reference to the embodiments. It should be noted that: unless otherwise specified, the conditions in the following embodiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following embodiments can be obtained from commercially available sources.
[0019] Example Example 1 A separator material for lithium batteries includes a base film and a modified nano-TiO2 coating. The modified nano-TiO2 coating is disposed on at least one side surface of the base film. The modified nano-TiO2 coating comprises the following raw materials in parts by weight: 55 parts of modified nano-TiO2 composite material, 8 parts of binder, 2.5 parts of dispersant, 3 parts of wetting agent, and 1 part of thickener. The modified nano-TiO2 composite material is prepared using cellulose nanocrystals, lanthanum zirconate, and rare earth praseodymium as modifiers and nano-TiO2 as raw material. The mass ratio of cellulose nanocrystals, lanthanum zirconate, and rare earth praseodymium is 5:2:1.
[0020] The preparation method of modified nano-TiO2 composite material includes the following steps: S1: Disperse cellulose nanocrystals in water, add nano-TiO2 suspension, the mass ratio of cellulose nanocrystals to nano-TiO2 is 1:5, and sonicate to obtain the composite. S2: Lanthanum zirconate and rare earth praseodymium were prepared by ion doping to obtain lanthanum zirconate loaded with rare earth praseodymium. S3: The composite was dispersed in ethanol, lanthanum zirconate-supported rare earth praseodymium powder was added, ultrasonic treatment was performed, tetrabutyl titanate was added dropwise, and the mixture was stirred to form a gel. After drying, the modified nano-TiO2 composite material was obtained.
[0021] The base membrane is a polyolefin microporous membrane; the binder includes soft monomers and hard monomers, the soft monomers include acrylates, the hard monomers include (meth)acrylonitrile, and the molar ratio of soft monomers to hard monomers is 1.5.
[0022] The dispersant is sodium polyacrylate; the wetting agent is a silanol nonionic surfactant; and the thickener is sodium hydroxymethyl cellulose.
[0023] A method for preparing a separator material for lithium batteries includes the following steps: (1) Weigh each raw material according to the weight parts, dissolve the binder in N-methylpyrrolidone, add the modified nano-TiO2 composite material, dispersant, wetting agent and thickener, mix and disperse in a ball mill jar to obtain nano-TiO2 composite material coating slurry; (2) The nano-TiO2 composite material coating slurry is coated on one side of the base film, and the thickness of the nano-TiO2 composite material coating on one side is 2.0 μm. After drying and winding, a lithium-ion battery separator is prepared.
[0024] Example 2 A separator material for lithium batteries includes a base film and a modified nano-TiO2 coating. The modified nano-TiO2 coating is disposed on at least one side surface of the base film. The modified nano-TiO2 coating comprises the following raw materials in parts by weight: 65 parts of modified nano-TiO2 composite material, 18 parts of binder, 5 parts of dispersant, 4 parts of wetting agent, and 2 parts of thickener. The modified nano-TiO2 composite material is prepared using cellulose nanocrystals, lanthanum zirconate, and rare earth praseodymium as modifiers and nano-TiO2 as raw material. The mass ratio of cellulose nanocrystals, lanthanum zirconate, and rare earth praseodymium is 3:2:1.
[0025] The preparation method of modified nano-TiO2 composite material includes the following steps: S1: Disperse cellulose nanocrystals in water, add nano-TiO2 suspension, the mass ratio of cellulose nanocrystals to nano-TiO2 is 1:3, and sonicate to obtain the composite. S2: Lanthanum zirconate and rare earth praseodymium were prepared by ion doping to obtain lanthanum zirconate loaded with rare earth praseodymium. S3: The composite was dispersed in ethanol, lanthanum zirconate-supported rare earth praseodymium powder was added, ultrasonic treatment was performed, tetrabutyl titanate was added dropwise, and the mixture was stirred to form a gel. After drying, the modified nano-TiO2 composite material was obtained.
[0026] The base membrane is a polyolefin microporous membrane; the binder includes soft monomers and hard monomers, the soft monomers include acrylates, the hard monomers include (meth)acrylonitrile, and the molar ratio of soft monomers to hard monomers is 2.5.
[0027] The dispersant is sodium polyacrylate; the wetting agent is a silanol nonionic surfactant; and the thickener is sodium hydroxymethyl cellulose.
[0028] A method for preparing a separator material for lithium batteries includes the following steps: (1) Weigh each raw material according to the weight parts, dissolve the binder in N-methylpyrrolidone, add the modified nano-TiO2 composite material, dispersant, wetting agent and thickener, mix and disperse in a ball mill jar to obtain nano-TiO2 composite material coating slurry; (2) The nano-TiO2 composite material coating slurry is coated on one side of the base film. The thickness of the nano-TiO2 composite material coating on one side is 3.5 μm. After drying and winding, a lithium-ion battery separator is prepared.
[0029] Example 3 A separator material for lithium batteries includes a base film and a modified nano-TiO2 coating. The modified nano-TiO2 coating is disposed on at least one side surface of the base film. The modified nano-TiO2 coating comprises the following raw materials in parts by weight: 80 parts of modified nano-TiO2 composite material, 24 parts of binder, 7.5 parts of dispersant, 5 parts of wetting agent, and 3 parts of thickener. The modified nano-TiO2 composite material is prepared using cellulose nanocrystals, lanthanum zirconate, and rare earth praseodymium as modifiers and nano-TiO2 as raw material. The mass ratio of the cellulose nanocrystals, lanthanum zirconate, and rare earth praseodymium is 5:2:1.
[0030] The preparation method of modified nano-TiO2 composite material includes the following steps: S1: Disperse cellulose nanocrystals in water, add nano-TiO2 suspension, the mass ratio of cellulose nanocrystals to nano-TiO2 is 1:4, and sonicate to obtain the composite. S2: Lanthanum zirconate and rare earth praseodymium were prepared by ion doping to obtain lanthanum zirconate loaded with rare earth praseodymium. S3: The composite was dispersed in ethanol, lanthanum zirconate-supported rare earth praseodymium powder was added, ultrasonic treatment was performed, tetrabutyl titanate was added dropwise, and the mixture was stirred to form a gel. After drying, the modified nano-TiO2 composite material was obtained.
[0031] The base membrane is a polyolefin microporous membrane; the binder includes soft monomers and hard monomers, the soft monomers include acrylates, the hard monomers include (meth)acrylonitrile, and the molar ratio of soft monomers to hard monomers is 6.3.
[0032] The dispersant is sodium polyacrylate; the wetting agent is a silanol nonionic surfactant; and the thickener is sodium hydroxymethyl cellulose.
[0033] A method for preparing a separator material for lithium batteries includes the following steps: (1) Weigh each raw material according to the weight parts, dissolve the binder in N-methylpyrrolidone, add the modified nano-TiO2 composite material, dispersant, wetting agent and thickener, mix and disperse in a ball mill jar to obtain nano-TiO2 composite material coating slurry; (2) The nano-TiO2 composite material coating slurry is coated on one side of the base film, and the thickness of the nano-TiO2 composite material coating on one side is 5.0 μm. After drying and winding, a lithium-ion battery separator is prepared.
[0034] Comparative Example 1 The difference from Example 1 is that no modified nano-TiO2 composite material was added.
[0035] Comparative Example 2 The difference from Example 1 is that the modified nano-TiO2 composite material is replaced with nano-TiO2.
[0036] Comparative Example 3 The difference from Example 1 is that no cellulose nanocrystals were added to the modified nano-TiO2 composite material.
[0037] The performance of the lithium battery separator was tested according to GB / T36363-2018, specifically for its needle penetration strength and thermal shrinkage. The data obtained are shown below: Table 1 Performance Test Results As can be seen from the data in Table 1, the diaphragms prepared in Examples 1-3 of this invention exhibit good needle penetration strength, excellent electrolyte wettability, low thermal shrinkage, and good thermal stability. This demonstrates that by adding modified nano-TiO2 composite materials, nanoparticles are introduced into the diaphragm to form a three-dimensional network structure, improving the diaphragm's liquid absorption and ionic conductivity, while also achieving high air permeability and good mechanical properties and ionic conductivity.
[0038] The above description is merely an exemplary embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. A separator material for lithium batteries, characterized in that, The invention comprises a base film and a modified nano-TiO2 coating. The modified nano-TiO2 coating is disposed on at least one surface of the base film. The modified nano-TiO2 coating comprises the following raw materials in parts by weight: 55-80 parts of modified nano-TiO2 composite material, 8-24 parts of binder, and 2.5-7.5 parts of dispersant. The modified nano-TiO2 composite material is prepared using cellulose nanocrystals, lanthanum zirconate, and rare earth praseodymium as modifiers and nano-TiO2 as raw material. The mass ratio of the cellulose nanocrystals, lanthanum zirconate, and rare earth praseodymium is 1-5:2-3:
1. The preparation method of the modified nano-TiO2 composite material includes the following steps: S1: Disperse cellulose nanocrystals in water, add nano-TiO2 suspension, the mass ratio of cellulose nanocrystals to nano-TiO2 is 1:3-5, and sonicate to obtain the composite. S2: Lanthanum zirconate and rare earth praseodymium were prepared by ion doping to obtain lanthanum zirconate loaded with rare earth praseodymium. S3: The composite was dispersed in ethanol, lanthanum zirconate-supported rare earth praseodymium powder was added, ultrasonic treatment was performed, tetrabutyl titanate was added dropwise, and the mixture was stirred to form a gel. After drying, the modified nano-TiO2 composite material was obtained. The adhesive comprises soft monomers and hard monomers, the soft monomers comprising acrylates, and the hard monomers comprising one or more of (meth)acrylonitrile, acrylonitrile, styrene, and (meth)acrylates, wherein the molar ratio of the soft monomers to the hard monomers is 1.5-6.
3.
2. The separator material for lithium batteries according to claim 1, characterized in that, The base membrane is a polyolefin microporous membrane.
3. The separator material for lithium batteries according to claim 1, characterized in that, The dispersant is one or more of sodium polyacrylate, lithium polyacrylate, potassium polyacrylate, and ammonium polyacrylate.
4. The separator material for lithium batteries according to claim 1, characterized in that, It also includes a wetting agent and a thickener, wherein the wetting agent is a silanol nonionic surfactant; and the thickener is sodium hydroxymethyl cellulose.
5. The method for preparing the separator material for lithium batteries according to any one of claims 1-4, characterized in that, Includes the following steps: (1) Weigh each raw material according to the weight parts, dissolve the binder in N-methylpyrrolidone, add the modified nano-TiO2 composite material, dispersant, wetting agent and thickener, mix and disperse in a ball mill jar to obtain nano-TiO2 composite material coating slurry; (2) The nano-TiO2 composite material coating slurry is coated on one side of the base film, dried and rolled up to prepare a lithium-ion battery separator.
6. The method for preparing the separator material for lithium batteries according to claim 5, characterized in that, The thickness of the nano-TiO2 composite material coating on one side is 2.0-5.0 μm.
7. A lithium-ion battery, characterized in that, Includes the separator material for lithium batteries as described in any one of claims 1-4.
Citation Information
Patent Citations
Nanometer coating liquid, preparation method thereof and nanometer coating diaphragm
CN120310342A